Ageing and physical function in East African foragers and pastoralists - Sayre, M. Katherine (Philos Trans R Soc Lond B Biol Sci, 2020)
Human lifespans are exceptionally long compared with those of other primates. A key element in exploring the evolution of human longevity is understanding how modern humans grow older. Our current understanding of common age-related changes in human health and function stems mostly from studies in industrialized societies, where older adulthood is often associated with an increased incidence of chronic diseases. However, individuals who engage in different lifestyles across industrialized and non-industrialized contexts may display variance in age-related changes in health and function. Here, we explore aspects of physical function in a non-industrialized context using three objective measures of physical function. We assessed physical activity levels, walking endurance and muscle strength in two East African populations: Hadza hunter–gatherers in Tanzania and Pokot pastoralists in Kenya. Both Hadza and Pokot participants displayed significant age-related differences in most, but not all, functional measures. Our results suggest that some age-related differences in physical function seen in industrialized contexts could be consistently experienced by most humans, while other age-related differences may vary across populations. Studies of ageing should expand to include a broad range of populations so we can create a more comprehensive understanding of how senescence varies across different lifestyle contexts. This article is part of the theme issue ‘Evolution of the primate ageing process’.